In Vitro Osteogenic Potential of Green Fluorescent Protein Labelled Human Embryonic Stem Cell-Derived Osteoprogenitors - Intekhab Islam; Gopu Sriram; Mingming Li; Yu Zou; Lulu Li; Harish K. Handral; Vinicus Rosa; Tong Cao (Stem Cells International)
Cellular therapy using stem cells in bone regeneration has gained increasing interest. Various studies suggest the clinical utility of osteoprogenitors-like mesenchymal stem cells in bone regeneration. However, limited availability of mesenchymal stem cells and conflicting evidence on their therapeutic efficacy limit their clinical application. Human embryonic stem cells (hESCs) are potentially an unlimited source of healthy and functional osteoprogenitors (OPs) that could be utilized for bone regenerative applications. However, limited ability to track hESC-derived progenies in vivo greatly hinders translational studies. Hence, in this study, we aimed to establish hESC-derived OPs (hESC-OPs) expressing green fluorescent protein (GFP) and to investigate their osteogenic differentiation potential in vitro. We fluorescently labelled H9-hESCs using a plasmid vector encoding GFP. The GFP-expressing hESCs were differentiated into hESC-OPs. The hESC-OPsGFP+ stably expressed high levels of GFP, CD73, CD90, and CD105. They possessed osteogenic differentiation potential in vitro as demonstrated by increased expression of COL1A1, RUNX2, OSTERIX, and OPG transcripts and mineralized nodules positive for Alizarin Red and immunocytochemical expression of osteocalcin, alkaline phosphatase, and collagen-I. In conclusion, we have demonstrated that fluorescently labelled hESC-OPs can maintain their GFP expression for the long term and their potential for osteogenic differentiation in vitro. In future, these fluorescently labelled hESC-OPs could be used for noninvasive assessment of bone regeneration, safety, and therapeutic efficacy.